Higher learning institutions electricity demand forecast by using moving average and winters method - Nuramirah Akrom, 1990-; Zuhaimy Ismail, supervisor; Fakulti Sains (2012)
Project Paper (Sarjana Muda Sains (Matematik Industri)) - Universiti Teknologi Malaysia, 2012